Regulating small public service vehicles in Ireland: Is there a problem of oversupply? - Paul K. Gorecki (The Economic and Social Research Institute (ESRI), 2012)
The small public service vehicle (SPSV) market in Ireland appears to have adjusted well to the changed economic circumstances. The reduction in demand for SPSV services occasioned by the recession has been met by a price and quantity adjustment. Prices are regularly discounted off the regulated maximum fare, while the number of SPSV operators has dropped by about 6 per cent per year since 2010. Estimates of oversupply of 13 to 22 per cent, albeit arguably biased upwards, are likely to be eliminated by the end of 2013/early 2014 at the earliest, and 2015/16 at the latest. Strategies have been put in place to deal with non-compliance with social welfare and tax rules. Hence for the Taxi Regulation Review Group in its December 2011 Report to base recommendations for extensive policy intervention on the view: (i) that there is considerable oversupply of SPSV services; (ii) that this is influenced in an important way by non-compliant operators; and, (iii) there is low exit from the industry is incorrect. Indeed, these recommendations which are being implemented, while no doubt containing sensible suggestions with regard to wheelchair accessible services and rural hackney services, at the same time will have the effect of reducing the flexibility of the SPSV market based on a model that seeks to favour the role of full time taxi operator. When combined with the 2010 prohibition on the issuing of new taxi and hackney licences, there is a real danger that when the economy revives and demand for SPSV services increases that there will be increased waiting times as they were in the 1990s when taxi numbers were restricted. There is an urgent need to reconsider these policy initiatives.
Keywords: 330